Integrative Grammar In Teaching Academic Writing The Case Of The Fourth Semester Students Atthe English Department Of IKIP PGRI Semarang - Ouwpoly, Nicolas Lodawik ((JELE) Journal Of English Language and Education, 2015)
This paper addresses the issue of academic writing teaching by using integrativegrammar to English Department of IKIP PGRI students with the focus on form and meaning. A method of integrative grammar, consisting of three major stages (a)Â exploration, (b) explanation, and (c) expression (EEE), is proposed. To inform how each of these stages function, several lessons were conducted by using those stages in the class of academic writing as the evidence. The paper describes and discusses the lessons themselves, their rationale, and their implementation of the proposed method. Â  checklist which was used to describe the activeness of the lecturer taught academic writing byusing EEE methods andquestionnaire conducted before and after the lessons and also the revision of the sillabus and lesson plan usedshowthat students preferred to write academically in L2 using the EEE method which not only focuses onform-based but also meaning-based.